RISK MANAGEMENT THROUGH LANDSLIDE BACK ANALYSIS IN GRASBERG MINE, PAPUA (Prosiding Temu Profesi Tahunan PERHAPI, 2020)
Grasberg is an ‘ultra-deep’ open pit copper-gold mine located in the highland of Jayawijaya mountain range of Papua province, Indonesia. Throughout its long history, Grasberg had critical geotechnical challenges that pose a threat to their operational and mining infrastructures. Landslide is one of the geotechnical hazards that has extreme potential damage that need to be further addressed. In general, one of the routines for approaching landslide behavior is through numerical analysis which is called a runout analysis.There are three main tasks to run this analysis:1. Modeling back-analysis on the past landslide events at Grasberg to define behavioral parameters that meet its actual components namely maximum distance reached, thickness, and deposits distribution of debris flows. 2. Prediction of upcoming model of landslide events that incorporating mm precision topographical survey and detailed geological structure identification via laser scanning as a reasonable landslide’s thickness limit.3. Development of risk management based on predictive landslide model and working criteria as a guidance for mine operation The combination of runout analysis and slope movement criteria which was provided by radar monitoring will give clear guidance and required action plans from mining operation team to address potential landslide issues in the mine to provide safe-productive mine operation.